Effect of dietary bile acids supplementation on growth performance, feed utilization, intestinal digestive enzyme activity and fatty acid transporters gene expression in juvenile leopard coral grouper (Plectropomus leopardus) - Gao, Yujie; Yao, Yifan; Huang, Jie; Sun, Yuejia; Wu, Qingjun; Guo, Dingqian; Wang, Shengpeng (Frontiers in Marine Science, 2023)
This study aimed to evaluate the effects of dietary bile acids on growth performance, feed utilization, body composition, digestive enzyme activity, and related gene expression in juvenile leopard coral grouper (Plectropomus leopardus). Five diets with varying levels of dietary bile acids (0, 0.15, 0.3, 0.45 and 0.6%) were formulated and each diet was fed to triplicate groups of 15 fish (13.14 ± 0.14 g) for ten weeks. Results showed that the significant enhancement in weight gain (WG) and specific growth rate (SGR) was observed in fish fed 0.3% bile acids (P < 0.05). Additionally, feed conversion ratio (FCR) was significantly improved with bile acids inclusion (P < 0.05). Higher feed intake was also recorded in bile acids inclusion groups, and significantly up-regulated gene expression of hypothalamus neuropeptide Y (NPY) was found in 0.3% group compared with the control group (P < 0.05). Dietary bile acids (0.3%) significantly decreased lipid deposition in the whole-body (P < 0.05), and lower hepatosomatic index (HSI) and viscerosomatic index (VSI) were also found in this group. Moreover, intestinal trypsin and lipase activities were significantly increased in 0.3% group (P < 0.05) to promote feed digestion. In addition, the relative expression levels of intestinal fatty acid binding protein 2 (FABP2) significantly up-regulated with inclusion of dietary bile acids, suggesting an enhancement of fatty acid transport (P < 0.05). In contrast, cholesterol transport related genes NPC1 like intracellular cholesterol transporter 1 (NPC1L1) and CD36 were notably down-regulated as bile acids inclusion (P < 0.05). This study provides valuable information for the formulation of diets for juvenile coral trout and indicates that dietary bile acids could potentially be used to improve growth performance and feed utilization.